IMPLEMENTASI ASSET HEALTH MANAGEMENT (STUDI KASUS PABRIK NPK) - Anisa, Nurfadilah (Jurusan Teknologi Industri dan Proses, 2024)
Effective asset management is a crucial factor in improving the efficiency and reliability of industrial equipment. However, in the implementation of technology-based asset management, an imbalance remains between the availability of equipment condition data and its utilization in maintenance decision-making. This study aims to evaluate the level of Asset Health Management (AHM) implementation through the use of the MX application and to identify issues that hinder comprehensive AHM implementation. The results show that the level of AHM implementation varies across equipment types, with 90% for mechanical equipment, 16% for instrument equipment, and 70% for electrical equipment. Of the 224 pieces of equipment registered in the AHM system, 7% had blank indicators due to unavailability of measurement data (no measurement) and 3% due to the absence of condition indicators (no indicator). In addition, several pieces of equipment were identified as being in critical high and caution high conditions, which could potentially reduce operational reliability if not addressed promptly. Based on the analysis, proposed improvements focused on adding measurement parameters and condition indicators to equipment experiencing blank indicators, as well as adjusting condition-based maintenance strategies for equipment with critical high and caution high status, such as measuring tire displacement against the shell, monitoring bucket condition, and inspecting thrust roller bearings. The implementation of this proposal is expected to improve the consistency of AHM implementation and support the optimization of MX application-based maintenance strategies.